Chronic physical exercise increases a neurogenesis marker within hippocampus (Medical Journal of Indonesia, 2018)
Background:Aerobic and anaerobic physical exercises conducted in both acute and chronic are really essential in keeping the body especially brain healthy. Physical exercise plays an important role in molecular system and is beneficial for the brain by enhancing neurogenesis which is mediated by the increase of BDNF level. This study aimed to evaluate the effect of physical exercise to the BDNF level of hippocampus tissues in Wistar rats. Methods: Thirty male rats were divided into five groups i.e. control group, acute aerobic physical exercise group, acute anaerobic physical exercise group, chronic aerobic physical exercise group, and chronic anaerobic physical exercise group. Physical exercises were conducted on animal treadmill. The level of hippocampus BDNF was determined using ELISA. The data were analyzed using independent t-test. Results: BDNF average levels of chronic aerobic and anaerobic physical exercises were higher than those of acute ones (152.86±1.62 pg/ml and 122.22±1.53 pg/ml vs 59.38±6.10 pg/ml and 54.05±3.35 pg/ml). There were significant differences in the BDNF average levels of hippocampus tissues between aerobic and anaerobic groups, in both acute and chronic exercise.Conclusion: The chronic physical exercises, both aerobic or anaerobic, are increasing higher the level of BDNF in brain tissue.